EFFECT OF BODY CONDITION SCORE AND FERTILITY STATUS ON PROTEINS AND MICRO-MINERALS PROFILE OF ESTRUAL MUCUS IN GIR COWS - GOHEL, M M; KAVANI, F S; HADIYA, K K (The Indian Journal of Animal Reproduction, 2023)
A total fifty Gir cows of different reproductive status ( 1 O=normal cyclic, 20=repeat breeders and 20=i nducedestrus) were selected to determine total proteins and micro-minerals profile in their estrual cervico-vaginal mucus(CVM) in relation to body condition score (on 0-5 point scale) and fertility post-Al. The overall mean concentrationsof total protein (g/dl) and micro-minerals, viz, copper, iron, zinc and manganese (ppm) in CVM of these cows were3.48±0. 04, 0 .90±0. 06, 9. 78±0.38, 1. 02±0. 04 and 1. 75±0.10, respectively. Total protein content of CVM was neitherinfluenced by groups, conception nor body condition score (BCS). The concentrations of copper and manganesewere significantly lower (P
Keywords: Gir cows; Est,rual cervical mucus; Total protein; Micro-minerals profile; BCS; Fertility